Validation of Using Multiplex PCR with Sex Markers SSM4 and ALLWSex2 in Long-Term Stored Blood Samples to Determine Sex of the North American Shortnose Sturgeon (Acipenser brevirostrum) - Hajar Sadat Tabatabaei Pozveh; Salar Dorafshan; Tillmann J. Benfey; Jason A. Addison; Matthew K. Litvak (Fishes, 2025)
Sex-specific information is crucial for sturgeon culture, conservation, and fisheries management. However, identifying their sex is difficult outside the spawning season. Two recently identified female-specific loci (AllWSex2 and SSM4) are conserved across many Acipenserid species, but they have not been validated for all species within this family. This study aimed to (1) determine whether SSM4 can be used to sex shortnose sturgeon, (2) develop and test a multiplex PCR technique using both ALLWSex2 and SSM4 for sexing shortnose sturgeon, (3) determine if long-term stored blood samples can be used to sex shortnose sturgeon, and (4) test the effect of storage temperature on DNA degradation. DNA was extracted from frozen RBC samples from 36 previously sexed fish. A multiplex PCR was set up using three pairs of primers: AllWSex2 and SSM4, as female-specific loci, and mtDNA, as an internal control. AllWSex2 and SSM4 allowed for perfect discrimination of sex. While long-term storage and storage temperature did cause DNA degradation, the signal was still strong enough after 8 years of cold storage for reliable sex determination. This suggests that researchers now have the ability to re-examine archived/frozen samples to determine the sex of their sturgeon.

Twentieth century extreme precipitation detected in a high-resolution, coastal lake-sediment record from California - Clarke A. Knight; David B. Wahl; Jason Addison; Mark Baskaran; R. Scott Anderson; Marie R. Champagne; Lysanna Anderson; Liubov Presnetsova; Beth Caissie; Scott Starratt (Journal of Paleolimnology, 2025)
California faces increasing economic and societal risks from extreme precipitation and flooding associated with atmospheric rivers (ARs) under projected twenty-first century climate warming. Lake sediments can retain signals of past extreme precipitation events, allowing reconstructions beyond the period of instrumental records. Here, we calibrate AR-related extreme precipitation from the last century to proxy data from lake sediments collected in the latitudinal zone of the highest frequency landfall for modern ARs in California. Excursions in erosional proxy data (Ti/Al) are positively and significantly correlated (r median = 0.45, p median = 0.04) with modern records of integrated vapor transport (IVT, kg m −1 s −1 ), a key metric of AR intensity, using correlations that incorporate age-model uncertainty. Despite the land-use change near the study site, the data suggest intense and long-lasting AR storms are identifiable in this sedimentary record. These results allow conservative inferences concerning past extreme hydrology at this site.

Multiscale patterns of genetic structure in a marine snail (Solenosteira macrospira) without pelagic dispersal - Stephanie J. Kamel; Richard K. Grosberg; Jason A. Addison (Marine Biology, 2014)

Multiple gene genealogies reveal asymmetrical hybridization and introgression among strongylocentrotid sea urchins - JASON A. ADDISON; GRANT H. POGSON (Molecular Ecology, 2009)
The evolution of incompatibilities between eggs and sperm is thought to play important roles in establishing and maintaining reproductive isolation among species of broadcast‐spawning marine invertebrates. However, the effectiveness of gametic isolation in initiating the speciation process and/or in limiting the introgression of genes among species at later stages of divergence remains largely unknown. In the present study, we collected DNA sequence data from five loci in four species of Strongylocentrotus sea urchins ( S. droebachiensis , S. pallidus , S. purpuratus , and S. franciscanus ) to test whether the susceptibility of S. droebachiensis eggs to fertilization by heterospecific sperm results in gene flow between species. Despite the potential for introgression, a small but statistically significant signal of introgression was observed only between the youngest pair of sister taxa ( S. pallidus and S. droebachiensis ) that was strongly asymmetrical (from the former into the latter). No significant gene flow was observed for either S. purpuratus or S. franciscanus despite the ability of their sperm to readily fertilize the eggs of S. droebachiensis . Our results demonstrate that asymmetrical gamete compatibilities in strongylocentrotids can give rise to asymmetrical patterns of introgression but suggest that gamete traits alone cannot be responsible for maintaining species integrities. The genetic boundaries between strongylocentrotid urchin species in the northeast Pacific appear to be related to postzygotic isolating mechanisms that scale with divergence times and not intrinsic gametic incompatibilities per se .

Range‐wide genetic homogeneity in the California sea mussel ( Mytilus californianus ): a comparison of allozymes, nuclear DNA markers, and mitochondrial DNA sequences - JASON A. ADDISON; BRIAN S. ORT; KATHRYN A. MESA; GRANT H. POGSON (Molecular Ecology, 2008)
We tested for genetic differentiation among six populations of California sea mussels ( Mytilus californianus ) sampled across 4000 km of its geographical range by comparing patterns of variation at four independent types of genetic markers: allozymes, single‐copy nuclear DNA markers, and DNA sequences from the male and female mitochondrial genomes. Despite our extensive sampling and genotyping efforts, we detected no significant differences among localities and no signal of isolation by distance suggesting that M. californianus is genetically homogeneous throughout its range. This concordance differs from similar studies on other mytilids, especially in the role of postsettlement selection generating differences between exposed coastal and estuarine habitats. To assess if this homogeneity was due to M. californianus not inhabiting estuarine environments, we reviewed studies comparing allozymes with other classes of nuclear DNA markers. Although both types of markers gave broadly consistent results, there was a bias favouring studies in which allozymes were more divergent than DNA markers (nine to three) and a disproportionate number of these cases involved marine taxa (seven). Furthermore, allozymes were significantly more heterogeneous than DNA markers in three of the four studies that sampled coastal and estuarine habitats. We conclude that the genetic uniformity exhibited by M. californianus may result from a combination of extensive gene flow and the lack of exposure to strong selective gradients across its range.